Resistensi Nelayan Terhadap Biaya Tambat Labuh Kapal Di Pelabuhan Perikanan Samudera Cilacap: Analisis Teori Resistensi James C. Scott - Kensiwi, Noni; Subekti, Fiqi Restu (Jurnal DinamikA, 2025)
This research stems from the issue of mooring fees at Cilacap Ocean Fisheries Port, which are considered burdensome for the fishermen. Regulation of the Central Government Number 85 of 2021 has triggered several protests as a form of resistance by the fishermen. This is because the government policy has disadvantaged them. As a result of this harmful policy, the fishermen did not remain passive but have repeatedly resisted the policy. Based on this issue, this study aims to identify the forms of resistance against the mooring fees at Cilacap Ocean Fisheries Port that are burdensome to the fishermen. To analyze these forms of resistance, the study uses James Scott's theory of resistance. The research employs a qualitative method with two types of research: literature review and field research through a case study approach. The research findings show that covert forms of resistance, such as gossiping, informal gatherings among fishermen, and the withdrawal of respect from the government, are more dominant or frequently practiced. This is because fishermen find it easier to meet and gather whenever they want. In contrast, overt resistance such as demonstrations, petition signings, and public hearings require the mobilization of masses and various preparations, making them less frequently carried out. Although overt resistance is less commonly practiced than covert resistance, it tends to be more effective in helping fishermen oppose Government Regulation No. 85 of 2021. Through overt resistance such as demonstrations, petition signings, and public hearings, the aspirations of the fishermen become more audible to the government, particularly the Regional House of Representatives (DPRD) of Cilacap Regency and the Ministry of Marine Affairs and Fisheries. Although the regulation has not yet been amended, at the very least, the fishermen's aspirations have been conveyed through this form of overt resistance. Therefore, James Scott's theory of resistance is highly relevant in examining the fishermen's resistance to the mooring fees at Cilacap Ocean Fisheries Port.